2013
DOI: 10.1159/000347164
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Conversion during Laparoscopic Cholecystectomy: Retrospective Analysis of Ten Years' Experience at a Single Tertiary Referral Centre

Abstract: Background/Purpose: Laparoscopic cholecystectomy (LC) is the standard treatment for symptomatic benign gallbladder disease. The identification of factors that reliably predict the need to convert LC to open cholecystectomy (OC) would help with patient education and counseling. Methods: Between January 2000 and December 2009, 4,698 patients underwent cholecystectomy. LC was attempted in 4,434 patients (94.4%) and OC from the start was performed in 264 patients (5.6%). The causes for conversion were evaluated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
1
18
2
2
Order By: Relevance
“…In our study, extensive peritoneal adhesions were responsible for 8.62% of the overall complication rate especially operative bleeding and conversion to open surgery. Many studies of same interest reported that previous upper abdominal surgery is associated with a higher rate of adhesions, an increased risk of operative complications, a greater conversion rate, a prolonged operating time and longer stay [4,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, extensive peritoneal adhesions were responsible for 8.62% of the overall complication rate especially operative bleeding and conversion to open surgery. Many studies of same interest reported that previous upper abdominal surgery is associated with a higher rate of adhesions, an increased risk of operative complications, a greater conversion rate, a prolonged operating time and longer stay [4,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Score of (0-5) indicates an easy approach while score of (6-10) indicates difficult approach and very difficult approach is observed with score of (11)(12)(13)(14)(15).…”
Section: Difficulty Scoringmentioning
confidence: 99%
“…Also, (Gholipour et al, 2009), in their study (Gholipour et al, 2009), which included 793 patients in 2009, introduced factors affecting the disease as leukocytosis (white blood cells more than 9,000). In addition, different researches (Jethwani et al, 2013;Sultan et al, 2013), identified leukocytosis as a risk factor for laparoscopic cholecystectomy conversion to open surgery. This finding was also emphasized in another study (Shiva, 2017), in which the researcher also cited leukocytosis as a risk factor for disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have identified male gender as a risk factor for transformation (Sultan et al, 2013;Lipman M et al, 2007) the exact explanation is not fully known but it may due to the fact that men are more tolerant to pain than women or reluctant or too busy to seek medical advice (Sultan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%